A randomised phase II trial and feasibility study of palliative chemotherapy in frail or elderly patients with advanced gastroesophageal cancer (321GO) - Hall, P; Lord, S; Collinson, M; Marshall, H; Jones, M; Lowe, C; Howard, H; Swinson, D; Velikova, G; Anthoney, A; Roy, R; Dent, J; et al. (Cancer Research UK, 2017)
BACKGROUND: Elderly patients are commonly under-represented in cancer clinical trials. The 321GO was undertaken in preparation for a definitive phase three trial assessing different chemotherapy regimens in a frail and/or elderly population with advanced gastroesophageal (GO) cancer. METHODS: Patients with advanced GO cancer considered unfit for conventional dose chemotherapy were randomly assigned in a 1 : 1 : 1 ratio to: epirubicin, oxaliplatin and capecitabine (EOX); oxaliplatin and capecitabine (OX); and capecitabine alone (X) (all 80% of full dose and unblinded). The primary end point was patient recruitment over an 18-month period. A registration study recorded treatment choice for all patients with advanced GO cancer at trial centres. RESULTS: A total of 313 patients were considered for palliative chemotherapy for GO cancer over the 18-month period: 115 received full dose treatment, 89 less than standard treatment or entered 321GO and 111 no treatment. Within 321GO, 55 patients were randomly assigned (19 to OX and X; 17 to EOX). Progression-free survival (PFS) for all patients was 4.4 months and by arm 5.4, 5.6 and 3.0 months for EOX, OX and X, respectively. The number of patients with a good overall treatment utility (OTU), a novel patient-centred endpoint, at 12 weeks was 3 (18%), 6 (32%) and 1 (6%) for EOX, OX and X, respectively. At 6 weeks, 22 patients (41%) had experienced a non-haematologic toxicity ⩾grade 3, most commonly lethargy or diarrhoea. The OTU was prognostic for overall survival in patients alive at week 12 (logrank test P=0.0001). CONCLUSIONS: It is feasible to recruit elderly and/or frail patients with advanced GO cancer to a randomised clinical trial. The OX is the preferred regimen for further study. Overall treatment utility shows promise as a comparator between treatment regimens for feasibility and randomised trials in the elderly and/or frail GO cancer population.